2021
DOI: 10.3857/roj.2021.00654
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy and safety of sequential neoadjuvant chemotherapy and short-course radiation therapy followed by delayed surgery in locally advanced rectal cancer: a single-arm phase II clinical trial with subgroup analysis between the older and young patients

Abstract: This study was performed to investigate the efficacy and safety of short-course radiation therapy (SCRT) and sequential chemotherapy followed by delayed surgery in locally advancer rectal cancer with subgroup analysis between the older and young patients. Materials and Methods: In this single-arm phase II clinical trial, eligible patients with locally advanced rectal cancer (T3-4 and/or N1-2) were enrolled. All the patients received a median three sequential cycles of neoadjuvant CAPEOX (capecitabine + oxalipl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
1

Year Published

2022
2022
2023
2023

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 29 publications
(40 reference statements)
0
0
1
Order By: Relevance
“…By adjusting for variables that could affect CSS and OS using PSM, we discovered that there was no signi cant difference in CSS OS between the surgery-only group and the combined treatment group. These ndings may contrast with certain studies that found neoadjuvant SCRT and sequential chemotherapy followed by delayed surgery to be safe and effective for older patients with locally advanced rectal cancer compared to younger patients [34]. While a combined therapy approach can reduce the extent of locally advanced rectal cancer and slightly decrease the likelihood of distant recurrence, older patients are exposed to the potential toxicity of doublet or triplet oxaliplatin-based therapy when receiving adjuvant chemotherapy after surgery, with questionable bene ts in the adjuvant and metastatic stages [35].…”
Section: Discussioncontrasting
confidence: 76%
“…By adjusting for variables that could affect CSS and OS using PSM, we discovered that there was no signi cant difference in CSS OS between the surgery-only group and the combined treatment group. These ndings may contrast with certain studies that found neoadjuvant SCRT and sequential chemotherapy followed by delayed surgery to be safe and effective for older patients with locally advanced rectal cancer compared to younger patients [34]. While a combined therapy approach can reduce the extent of locally advanced rectal cancer and slightly decrease the likelihood of distant recurrence, older patients are exposed to the potential toxicity of doublet or triplet oxaliplatin-based therapy when receiving adjuvant chemotherapy after surgery, with questionable bene ts in the adjuvant and metastatic stages [35].…”
Section: Discussioncontrasting
confidence: 76%